(untitled) - DWI KURNIAWATI, RAHAYU (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Activity and bustle or academic routines consisting of professors, Employees, and students at college each day. Addressing and understanding the material food providers that provide meals, drinks, and snacks for the students ' needs. Almost all of the university not to Miss FE Unesa already provides culinary needs, according to the place, the field by providing a cafe.The service quality can affect customer satisfaction toward a product especially in the field of services. A good quality of service at the Cafetaria Srikandi intended to create consumer satisfaction in the Cafetaria Srikandi,Faculty of Economics State University of Surabaya. This research intend to explain the influence of the quality of services to the consumer satisfaction at the Cafetaria Srikandi Faculty of Economics University of Surabaya either simultaneously or partial. This research was conducted with methods uses accidental sampling (part of non-probability sampling methods). The population in this study are all students of economic Faculties whom in the Cafetaria Shikhandi. A new sample used was 365 respondents. Kuantiatif data analysis include the assay validity, reliability, classic assumption test, analysis multiple regression, t-test, F-test, as well as the analysis of regression coefficients (R). Based on the adjusted R2 value 0,491-generated say influential consumer satisfaction service quality at the Cafetaria Srikandi Faculty of Economics State University of Surabaya of 49,1% while the rest of 50.9% influenced by variables other than research. The results showed that there was a simultaneous influence of quality of services to the satisfaction of consumers and partially only four variables that affect that is tangible, responsiveness, assurance and emphaty. While reliability has no effect on customer satisfaction. As for the results of the study indicate that the variable is a variable emphaty most dominant influence on consumer satisfaction in the Cafetaria Srikandi Faculty of Economics State University of Surabaya. Keywords: service quality, customer satisfaction.